PWE-336 Outcomes of colorectal cancer resections in patients with multiple co-morbidities and advanced tumours. (22nd June 2015) - Garry, J; Ormsby, N; Joshi, H; Goldsmith, P; Scott, M; Samad, A; Rajaganeshan, R
Abstract : Introduction: Comorbid patients with advanced tumours constitute a rapidly growing segment of patients undergoing colorectal cancer resection, but their outcomes remain understudied and under-reported. Our aims were to analyse outcomes of high risk patients with advanced tumours undergoing curative colorectal resections compared with a similar cohort 2 decades younger. Method: Data from a prospectively collected database of consecutive patients undergoing colorectal resection between 2011 and 2013 were analysed. Primary endpoints were 30-day mortality and morbidity. The secondary endpoint was long-term survival. Results: We identified 308 patients undergoing elective resections. Overall 30 and 60 day mortality was 2.3% and 4.5% respectively independent of tumour grade and age/ASA grade. In those with pT3–4 tumours, this was comparable (2.2% and 5.4%). In those who were ASA 3–4 this rose to 6.5% and 10.8%. We studied 66 consecutive patients with ASA grade 3–4 and pT3–4 cancers, including 22 over 80 years of age. This cohort demonstrates 6% mortality at 30 days and 10.4% at 90 days with a 25.4% complication rate. Amongst those 80 and above with ASA 3–4 and pT3–4 cancers, 30 and 90 day mortality was 13.6% and 18.2% respectively, with a 31.8% complication rate. Conclusion: Advanced tumour grade does not impact on 30 and 90-day survival following elective surgical resection. However ASA grade is the most significant factor affecting perioperative mortality. Octogenarians are more likely to have poor performance status, with limited physiological reserve. In these patients with advanced tumours and ASA3–4, there is a considerable increase in the perioperative risk. Resources should therefore be in place for postoperative high dependency care for this high-risk group. Disclosure of interest: None Declared.